2012
DOI: 10.1158/0008-5472.sabcs12-p1-12-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P1-12-01: Evaluation on efficacy and safety of capecitabine plus docetaxel versus docetaxel monotherapy in metastatic breast cancer patients pretreated with anthracycline: Results from a randomized phase III study (JO21095)

Abstract: Introduction: A previous large-scale phase III study demonstrated that, compared with docetaxel (T) alone, capecitabine (X) and T in combination (XT) offered significantly superior progression free survival (PFS) and overall survival (OS) in metastatic breast cancer (MBC). However, XT increased Grade 3/4 adverse events (AEs) which led to more frequent dose reductions than with T alone. Optimal dose of XT in Japanese was examined in a phase Ib study. Based on the background, we conducted a phase III randomized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A PRISMA flow diagram of the citation screening for the original and updated SRs is shown in Table 1 categorises included RCTs by treatment line, including key trial characteristics. Of the 14 second-and/or later-line papers, five [19][20][21][22][23] reported data for a purely second-line patient population, three [24][25][26] reported data from mixed-line treatment but provided results for the second-line subgroup separately, three [27][28][29] had unclear second-line status (i.e. it was unclear whether the previous therapy had been given in the adjuvant or metastatic setting), two [30,31] reported data from second-or later-line patients, and one [32] reported data from a second-or later-line subgroup separately.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A PRISMA flow diagram of the citation screening for the original and updated SRs is shown in Table 1 categorises included RCTs by treatment line, including key trial characteristics. Of the 14 second-and/or later-line papers, five [19][20][21][22][23] reported data for a purely second-line patient population, three [24][25][26] reported data from mixed-line treatment but provided results for the second-line subgroup separately, three [27][28][29] had unclear second-line status (i.e. it was unclear whether the previous therapy had been given in the adjuvant or metastatic setting), two [30,31] reported data from second-or later-line patients, and one [32] reported data from a second-or later-line subgroup separately.…”
Section: Resultsmentioning
confidence: 99%
“…Only three trials enrolled confirmed HER2-negative patients specifically [19,27,29] An overview of the patient characteristics across treatment arms is shown in Table 2. Within trials, there were some potential imbalances between treatment arms: the proportion of patients with oestrogen or progesterone receptor positivity (ER+ and/or PR+) in Baselga et al, 2012 [29] was numerically higher on sorafenib + capecitabine vs capecitabine; the proportion ER+ in Venturino et al, 2000 [20] was higher in the vinorelbine monotherapy arm; the proportion of patients with ECOG (Eastern Cooperative Oncology Group) status 0 was higher with docetaxel monotherapy vs docetaxel + gemcitabine in Papadimitriou et al, 2009 [23]; median ECOG status was lower in the vinorelbine monotherapy arm and the proportion of patients with visceral metastases also lower in Venturino et al, 2000 [20]; the proportion of patients with visceral metastases was numerically higher on mitomycin vs paclitaxel in Dieras et al, 1995 [21]; and median age was slightly higher in the epirubicin arm vs doxorubicin in Gasparini et al, 1991 [22].…”
Section: Study and Patient Level Characteristics Of Trials Enrolling mentioning
confidence: 99%
See 3 more Smart Citations